MENINGKATKAN KEMAMPUAN MENYELESAIKAN OPERASI HITUNG PERKALIAN MELALUI PENGGUNAAN MEDIA TALI PAS - Purwandari Suciningtyas (LPPM UNISDA, 2020)
This study aims to describe students' activeness of the class when it is applied to the media and the improvement of learning outcomes of the students of grade V SDN Paciran I Lamongan 2016/2017 academic year in completing multiplication counting operation through the use of laces. This research belongs to classroom action research. Data obtained in the form of formative test results, observation sheet of teaching and learning activities. The learning outcomes of multiply counting operations by applying the wrist strap medium from cycle 1 to cycle 2 experience, a very satisfactory improvement. In cycle 1, there is an increase of students who fulfill KKM that is 50%, while in cycle 2 reach 100%.